Kate and Milly in Henry James’s The Wings of the Dove - Dyah Aju Hermawati (Unipdu Jombang, 2021)
This article discusses women’s manners as seen in Henry James’s The Wings of the Dove. The Wings of the Dove is one of James’s work which becomes substancial and important novels on the international theme in the early of twentieth century. The women who will be observed are Kate Croy and Milly Theale as the representative of the nineteenth century women. The purpose of this discussion is to know Kate’s and Milly’s manners because of the background which molded them. To come to this purpose it will be examined the two factors that form their manners those are their educational background and the influence of their family circle or social condition around them. It can also be traced back from historical point of view that though most American people originally came from Europe; they developed a new set of social value after settling in America, as described in Henry James’s Novel The wings of the Dove.Key words : women; manner